Heteronormativity in narratives of fatherhood: Cross-cultural experience - Nduna, Mzikazi (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Morison, Tracy & Macleod, Catriona (2015) Men’s pathways to parenthood: Silence and heterosexual gendered norms. Cape Town: HSRC Press. ISBN 978-0-7969-2503-9 pbk. Pages ix + 197. This book discusses the experiences of White Afrikaans adult men and women’s parenting decision-making. In this book, the authors share insight on decision-making in relation to childbirth and childrearing from an under-researched South African community – those with distinctly Afrikaans heritage. The data shared in this book corrects some assumptions about childbirth. One of these is the assumption that childbirth is planned; and that for older, mature, parents the decision to have a child is a result of a deliberate and conscious decision-making exercise. The data presented from the authors’ research shows that even for married people, or older people, pregnancy just happens.